Bone cement cardiac and pulmonary embolism. Issue 8 (1st June 2017) - Cianciulli, Tomás F.; Mc Loughlin, Diego E.; Morita, Luis A.; Saccheri, María C.; Lax, Jorge A.
Abstract : This case describes a complication of bone cement use. A 65‐year‐old male patient with back spine trauma caused by a fall, underwent a percutaneous vertebroplasty. Five years later, he consulted for palpitations, and the electrocardiogram showed supraventricular arrhythmia. A transthoracic two‐dimensional echocardiography showed a hyperechogenic linear structure of 7 cm length, running from the lateral wall of the right ventricle to the right atrium through the tricuspid valve. This foreign body, which was suspicious for bone cement embolism, appeared rigid and was attached at the lateral wall of the right ventricle, with its proximal end free in the right atrium. The tip of the cement embolus was inside the myocardium of the lateral wall of the right ventricle, with risk of cardiac perforation. A fluoroscopy was performed, which confirmed the presence of cement within the right heart, with great mobility in each cardiac cycle. Chest computed tomography (CT) and multidetector CT three‐dimensional reconstruction confirmed the presence of cement within the right heart. Chest CT showed two pulmonary embolisms, one in the right upper lobe and one in the left lower pulmonary lobe. This case emphasizes the risk of late clinical manifestations of cardiac and pulmonary embolism of methylmethacrylate after percutaneous vertebroplasty, suggesting that the risk of such embolism might be underestimated. We propose routine chest radiography, two‐dimensional echocardiography, and chest CT after every percutaneous vertebroplasty, to detect asymptomatic cardiac and pulmonary embolism and thereby prevent serious delayed cardiopulmonary failures.